ABOUT THE NEW METHOD OF GAS FLARE SUPPRESSION - Semko, O. M.; Bezkrovna, M. V.; Vynohradov, S. A.; Yahudina, N. I. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The experimental researches of gas flame suppression by high speed pulse liquid jetі which are generated powder pulse hydro cannon were held. The velocity of the pulse jet was depended on charge energy and it ranged from 300 to 600 m/s. The flow photographing was held, the head jet velocity right near the gas flame was measured by laser non-contact measur-ing instrument. It is shown, that the high-speed cloud of splashes with the big cross-section which effectively forces down a flame of the gas flame on distances 5—20 m from installation, is formed round the pulse liquid jet of high speed.